Enabling Institutional Control for Project Risk Management in the Context of Digital Transformation - Abbas, Ahmed Hamzah; Mardan, Zaid Aed; Kadhim, Hayder Neamah (Indonesian Journal of Law and Economics Review, 2026)
<div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="56f4f11c-0134-4916-938b-de24300150b2" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> General Background: Rapid digital technological advancement has transformed business environments, increasing complexity and challenging traditional internal control systems. Specific Background: The integration of digital systems and artificial intelligence has reshaped management practices, requiring alignment between institutional control and project risk management. Knowledge Gap: Conventional control frameworks remain inadequate in addressing risks within dynamic digital transformation contexts. Aims: This study evaluates the activation of institutional control supported by digital systems in managing project risks. Results: Findings reveal a statistically significant relationship, with institutional control explaining 16.7% of variance in project risk management outcomes and strong agreement on ethical leadership and risk identification practices. Novelty: The study introduces an integrated framework combining institutional control, digital systems, and performance evaluation tools. Implications: Results emphasize the need for adaptive control frameworks, strengthened digital governance, and improved organizational coordination to support effective risk management in evolving digital environments. Highlights: • Strong Statistical Linkage Identified Between Control Activation and Risk Handling Outcomes • Leadership Ethics and Structured Identification Processes Show High Organizational Agreement • Integrated Framework Combining Governance Tools and Digital Infrastructure Proposed Keywords: Digital Transformation, Institutional Control, Project Risk Management, IT Governance, Performance Evaluation.